The East of the West. Harold J. Berman and Eastern Europe - Giaro, Tomasz (. Rechtsgeschichte. - Frankfurt am Main : Vittorio Klostermann GmbH, 2002-. - Online-Ressource. - ISSN 2195-9617. - urn:nbn:de:hebis:30:epflicht-172326 21, 2013)
During the late Middle Ages, the subject of Berman’s focus, the West, equalled a Europe whose overseas expansion had not yet begun. This recalls the "Europe of legal historians" as their attempt, efficiently caricatured by Dieter Simon, to determine the borders of the continent on the basis of a medieval state of affairs. Such a historical justification of geopolitical concepts is risky, but nonetheless common. In the Middle East, the borders of Biblical regions legitimize present or future frontiers. Berman shared the usual ideas of legal history as regards the modern being nothing else than a protraction or renewal of the old, when he identified the papal revolution of 1075 as the factor having durably impregnated western legal culture. ...